The Two sons of Prophet Adam(A.s) - Saniyasnain khan; Saniyasnain khan (UAE iqra book distribution)
Its a story of Hazrat Adam's two sond Habi;l and Qabil.This ia about their fight and murder of habil by qabil.It gives a lesson of not fight it just harms you and others.